Involvement of Academic Staff in the Practice of Professional Development - G. Z. Efimova (Высшее образование в России)
The article explores the level of involvement of scientific and pedagogical professionals in various social activities for professional development compared to other employee groups. It argues that obtaining additional professional training can be a valuable tool for career growth. The author sees professional development as an integral part of academic growth for scientific and educational workers, along with personal and career development. The findings are based on a combination of theoretical and empirical research conducted by domestic and international scholars, as well as official statistical data and the results of an original sociological study. The study involved a questionnaire survey of scientific and educational professionals (n = 223), as well as other employee groups (n = 833), in the Tyumen and Sverdlovsk regions. As a result, it was found that scientific and pedagogical workers are more likely to engage in professional development activities compared to other categories of the employed population. Continuing professional education programs appear to be the most common form of professional growth. Due to their specialized activities, academic staff tend to develop digital skills more often, while other groups develop personal skills to a greater degree. Based on the level of involvement in professional development, we identified five groups of respondents: “active and engaged”, “achieving the desired level or feeling disappointed”, “questioning or confused”, “recognizing the importance of professional development”, and “rejecting professional development”. The theoretical and empirical findings led to the development of potential strategies to enhance the engagement of scientific and educational professionals in ongoing skill development and acquisition of new competencies. This article is aimed at university management responsible for professional development of academic staff. The findings presented here may have practical implications for the development of personnel strategies at universities with the goal of increasing human capital and professional competence among academic staff, as well as motivating them to engage in continuous learning. The results of this study could be beneficial for participants in the academic community, as well as for specialists involved in developing educational programs and planning the future of universities strategically. The material presented in this paper is relevant not only for academic staff, but also for graduate students who are focused on their continuous professional growth within the academic sector.